ADMINISTRATIVE KNOWLEDGE IN INNOVATIVE DEVELOPMENT OF EDUCATIONAL INSTITUTIONS - Tatiana A. Pankratova; Zinaida V. Bragina (Статистика и экономика, 2016)
This article investigated the conditionsfor generating administrative knowledgeand ways to evaluate his conditionand optimization. Designated methodsand tools actualization administrative management of knowledge as aresource of innovative development ofthe educational institution. The basic directions of innovative development ofsoftware, including the assessment of theimpact of corporate culture, and diagnosisof barriers to educational institution.